Functional Analysis of the Stability Determinant AlfB of pBET131, a Miniplasmid Derivative of Bacillus subtilis (natto) Plasmid pLS32 - Tanaka, Teruo (American Society for Microbiology (ASM), 2010)
Bacillus subtilis plasmid pBET131 is a derivative of pLS32, which was isolated from a natto strain of Bacillus subtilis. The DNA region in pBET131 that confers segregational stability contains an operon consisting of three genes, of which alfA, encoding an actin-like ATPase, and alfB are essential for plasmid stability. In this work, the alfB gene product and its target DNA region were studied in detail. Transcription of the alf operon initiated from a σ(A)-type promoter was repressed by the alfB gene product. Overproduction of AlfA was inhibitory to cell growth, suggesting that the repression of the alf operon by AlfB is important for maintaining appropriate levels of AlfA. An electrophoretic mobility shift assay and footprinting analysis with purified His-tagged AlfB showed that it bound to a DNA region containing three tandem repeats of 8-bp AT-rich sequence (here designated parN), which partially overlaps the −35 sequence of the promoter. A sequence alteration in the first or third repeat did not affect the AlfB binding and plasmid stability, whereas that in the second repeat resulted in inhibition of these phenomena. The repression of alfA-lacZ expression was observed in the constructs carrying a mutation in either the first or third repeat, but not in the second repeat, indicating a correlation between plasmid stability, AlfB binding, and repression. It was also demonstrated by the yeast two-hybrid system that AlfA and AlfB interact with each other and among themselves. From these results, it was concluded that AlfB participates in partitioning pBET131 by forming a complex with AlfA and parN, the mode of which is typified by the type II partition mechanism.